2020
DOI: 10.48550/arxiv.2007.05505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Knowledge Extraction From Cloud Service Incidents

Abstract: In the last decade, two paradigm shifts have reshaped the software industry -the move from boxed products to services and the widespread adoption of cloud computing. This has had a huge impact on the software development life cycle and the DevOps processes. Particularly, incident management has become critical for developing and operating large-scale services. Incidents are created to ensure timely communication of service issues and, also, their resolution. Prior work on incident management has been heavily f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Shetty et al [6] proposed SoftNER: Software artifact Named-Entity Recognition, a framework for unsupervised named-entity recognition from cloud service incidents. It utilizes structural pattern extractors and label propagation to bootstrap training data.…”
Section: A Named-entity Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shetty et al [6] proposed SoftNER: Software artifact Named-Entity Recognition, a framework for unsupervised named-entity recognition from cloud service incidents. It utilizes structural pattern extractors and label propagation to bootstrap training data.…”
Section: A Named-entity Recognitionmentioning
confidence: 99%
“…Recent work has focused on various aspects of incident management such as machine learning models for incident triaging [2], [3], recommendation of troubleshooting guides for incident mitigation [4], and identifying related incident reports [5]. Shetty et al [6] did a large scale study of incident reports from Microsoft, and found that majority of these incident reports are unstructured. This makes any automation for handling these incidents nearly impossible.…”
Section: Introductionmentioning
confidence: 99%